Determination of Nutritional Values of Seedling Pumpkin (Cucurbita pepo L.) Residues Silage - Abdurrahman Pirinç; Abdullah Özbilgin; Oğuzhan Kahraman; Esad Sami Polat (Turkish Journal of Agriculture: Food Science and Technology, 2020)
In this study, nutritional values of silages made from seed pumpkin residues were investigated. Pumpkin residues collected from Konya region were put into silo in vacuum sacks with various additives. As additives, straw, inoculant containing lactic acid bacteria or a mixture of both in certain proportions were used. After the silos were opened, their pH was determined and then samples were taken to determine the essential fatty acid compositions and nutrient analyses were done. Natural pumpkin (Group 1), natural pumpkin + inoculant (100ppm) (Group 2), withered pumpkin + 15% straw (Group 3), withered pumpkin + 15% straw + inoculant (100ppm) (Group 4) such that the fourth group is formed. Dry matter values of pumpkin groups are Group 1 7.89%, Group 2 6.62%, Group 3 12.22% and Group 4 12.25% respectively. Their pH is 3.78 in Group 1, 3.71 in Group 2, 3.86 in Group 3 and 3.82 in Group 4. The crude protein ratio in the experimental groups was determined in the highest Group 2 (14.97%) and the lowest in Group 3 (10.56%). NDF rate was determined in the highest group 4 (49.74%) and the lowest in Group 2 (28.51%). In addition, the highest ADF rate was determined in Group 4 (37.91%) and the lowest in Group 2 (24.90%). There was a statistically significant difference between the research groups in terms of ethanol content. Acetic acid and propionic acid content was found statistically significant between groups. As a result, when the pumpkin residues are silaged, it can be used as feed material in animal feeding. In addition, it can be said that pumpkin residues can be evaluated in different areas in the high amount of Ethanol content resulting from silage production.